1998
DOI: 10.1111/j.1439-0523.1998.tb01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two new genes conferring resistance to rice blast in the Chinese native cultivar ‘Maowangu’

Abstract: The Chinese native rice cultivar 'Maowangu' expresses a high level of resistance to many races of rice blast (Pyricularia grisea) collected from North China and Japan. 'Maowangu' was crossed with 10 Japanese differential cultivars and the susceptible Chinese cultivar 'Lijiangxintuanheigu' (LTH). AUelism tests were conducted in the Fj populations with rice blast races. The resistance of 'Maowangu' was governed by two dominant genes which were non-allelic to the resistance genes at seven loci: Pi-a, Pi-i, Pi-k, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Over 25 blast R genes have been mapped on the rice genome, many of which are allelic or closely linked (Kiyosawa 1989;Inukai et al 1994;Wang et al 1994;Pan et al 1998;Chao et al 1999). For example, 5 blast R genes have been identified at the Pi-k locus of chromosome 11 (Kiyosawa 1989;Inukai et al 1994).…”
mentioning
confidence: 99%
“…Over 25 blast R genes have been mapped on the rice genome, many of which are allelic or closely linked (Kiyosawa 1989;Inukai et al 1994;Wang et al 1994;Pan et al 1998;Chao et al 1999). For example, 5 blast R genes have been identified at the Pi-k locus of chromosome 11 (Kiyosawa 1989;Inukai et al 1994).…”
mentioning
confidence: 99%
“…QTL qBLAST-2-2 was located in RM183-RM263 region on chromosome 2, on which three blast resistant genes Pi14, Pi16 (Pan et al 1998a(Pan et al , 1999, and Pid1 ) had been found. QTL qBLAST-6 was mapped to RM527-PSM136 region on chromosome 6.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, the authors have identiWed six R genes in Yunnan cvs, including Pi13 and Pi14 in cv. Maowangu (Pan et al 1998a), Pik-g in GA20 and Pi15 in cv. GA25 (Pan et al 1998b), Pi27 in cv.…”
Section: M11mentioning
confidence: 99%